Immersive Technology for Cognitive-Motor Training in Parkinson’s Disease - Lau, Justin; Regis, Claude; Burke, Christina; Kaleda, MaryJo; McKenna, Raymond; Muratori, Lisa M. (Frontiers in Human Neuroscience, 2022)
Background Parkinson’s disease (PD) is a neurodegenerative disease in which the progressive loss of dopaminergic neurons (DA) leads to initially sporadic and eventually widespread damage of the nervous system resulting in significant musculoskeletal and cognitive deterioration. Loss of motor function alongside increasing cognitive impairment is part of the natural disease progression. Gait is a complex motor behavior that requires components of attention and memory to prevent falls and injury. In addition, evidence points to the critical role of salient visual information to gait adaptability. There is a growing understanding that treatment for PD needs to address movement as it occurs naturally and walking needs to be practiced in more complex environments than traditional therapy has provided. Methods This single-blinded randomized-controlled study examined the feasibility and preliminary efficacy of a novel, immersive treadmill training. Eighteen participants with PD were randomized to either an experimental or control group. The intervention group trained for 30 minutes, three times/week for four weeks on a split belt treadmill combined with a first-person immersive video game. Assessment was repeated one-month after baseline. Gait velocity, 6MWT, TUG, TUG Cognitive, MoCA and SDMT served as preliminary outcomes. Results This novel treadmill training program was well-tolerated with all participants in the intervention group completing four weeks of training three times a week without any adverse effects. After immersive cognitive motor training, the experimental group made clinically relevant improvements in gait speed and walking distance during the 6MWT while members of the control group showed no change or decreased gait speed and walking distance over the one-month trial. In addition, the experimental group demonstrated significant improvement for the TUGCognitive and improved scores on MoCA and SDMT cognitive outcome measures while the control group did not. Conclusion The use of immersive gaming technology to engage specific areas of cognition related to gait is feasible in PD. The treadmill training program paired with a customized interactive video game improved walking velocity in addition to non-significant but consistent improvements in other gait measures and cognitive performance in participants with early to mid-stage PD.